2019
DOI: 10.1108/jbim-09-2017-0209
|View full text |Cite
|
Sign up to set email alerts
|

Must have or nice to have

Abstract: Purpose This paper aims to provide an opportunity to study organization buying behavior, specifically buying and selling in the B2B context. The case demonstrates the need to understand the expectations of the buyer’s decision-making unit and the challenges involved in acquiring and retaining customers based on the articulated value proposition of the product. The case also provides an opportunity to explore the critical issues related to an organization’s buying process, while emphasizing on the importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The foundations of OBB as a separate research discipline are found in the seminal work of Sheth, Webster and Wind and their colleagues (Robinson et al , 1967; Sheth, 1973, 1996; Webster, 1965; Webster and Wind, 1972; Wind and Webster, 1972). Today, OBB continues stimulating prolific research output (Bachkirov et al , 2016; Chavan et al , 2018; Haensel and Hofmann, 2018; Mogre et al , 2017; Kauffman, 1996; Lewin and Johnston, 1996; Liu and Chen, 2018; Mahapatra et al , 2018; Madhavaram et al , 2011; Wilson, 1996). Developing OBB models has become an established way of creating knowledge in the field, and a major review of foundational work (Johnston and Lewin, 1996) generated an overarching model of OBB that integrates previous conceptualizations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The foundations of OBB as a separate research discipline are found in the seminal work of Sheth, Webster and Wind and their colleagues (Robinson et al , 1967; Sheth, 1973, 1996; Webster, 1965; Webster and Wind, 1972; Wind and Webster, 1972). Today, OBB continues stimulating prolific research output (Bachkirov et al , 2016; Chavan et al , 2018; Haensel and Hofmann, 2018; Mogre et al , 2017; Kauffman, 1996; Lewin and Johnston, 1996; Liu and Chen, 2018; Mahapatra et al , 2018; Madhavaram et al , 2011; Wilson, 1996). Developing OBB models has become an established way of creating knowledge in the field, and a major review of foundational work (Johnston and Lewin, 1996) generated an overarching model of OBB that integrates previous conceptualizations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The committee at these three festivals grew awareness as a reference for artistic policy in curatorial. That awareness is the development of festivals as cultural events that must-have colorful variety and artistic intensity from various aspects of the cultural dynamics of oral traditions [32], [33]. Every work or repertoire in performance must reflect this concept, such as aesthetic content, various artistic signs, meanings, and the "roots" of art history for native speakers.…”
Section: Artistic Policymentioning
confidence: 99%
“…However, it is worth mentioning that marketing scholars recommend value-based pricing but do not proscribe the use of cost information. For instance, Mahapatra et al (2019) state the need to understand the buyers' expectations based on the articulated value proposition of the product independently of the use of cost information. In a rather practical sense, adopting a cost-plus formula does not prevent firms from using value information; consequently, it does not result in a mismatch between theory and practice.…”
Section: Introductionmentioning
confidence: 99%